1977
DOI: 10.1042/cs0530579
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Serum Ionized Calcium during Exercise

Abstract: 1. Normal subjects showed an average increase in serum ionized calcium (Ca2+) concentration of 0·11 mmol/l in peripheral venous blood 10 min after onset of bicycle exercise at 70% of maximum aerobic capacity. The corresponding mean rise in serum total calcium concentration was 0·21 mmol/l. 2. The change in serum Ca2+ as result of acidification was studied in 20 normal subjects by carbon dioxide equilibration in vitro followed by measurement of serum Ca2+. The log serum Ca2+ was inversely proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The current study examined a smaller number of horses, all of whom were clinically normal, but over a much wider range of blood pH. The inverse relationship between iCa and pH is similar to that observed in man during intense exercise (Nielsen et al 1977).…”
Section: Discussionsupporting
confidence: 59%
“…The current study examined a smaller number of horses, all of whom were clinically normal, but over a much wider range of blood pH. The inverse relationship between iCa and pH is similar to that observed in man during intense exercise (Nielsen et al 1977).…”
Section: Discussionsupporting
confidence: 59%
“…Finally, clenching the fist for as short a period as 1 minute during venous occlusion has been shown to cause an increase in lactate of 3 0-3 5 mmol/l and a decrease in venous pH to 7-10-7-15 (van Leeuwen et al, 1961), and intermittent fist-clenching once a second for 3 minutes during occlusion increases blood lactate by a mean of 4-5 mmol/l (Braybrooke et al, 1975). Direct measurement has shown that serum ionised calcium increases during exercise on a bicycle ergometer (Nielsen et al, 1977). Variation in forearm exercise, which causes hypoxia and dissociation of calcium bound to protein due to a fall in pH and to an increase in undissociated calcium lactate, might cause a variable decrease in the change of total calcium as albumin increases.…”
Section: Discussionmentioning
confidence: 99%
“…Ionised calcium concentrations of horses completing Phase D of the Endurance Test have previously been reported to be lower than values before the event (Geiser et al 1995). Serum ionised calcium concentrations of human individuals increase during exercise at 70% of maximal aerobic capacity, and the increase is related, at least in part, to a decrease in blood pH (Nielsen et al 1977). Three-day-event horses perform Phase D with heart rates approximately 75% of their estimated maximal heart rate .…”
Section: Variablementioning
confidence: 99%